Visual outcome, ocular findings, and visual quality of life in patients with Fabry disease. (2nd November 2022) - Nilsson, Mattias; Kolagari, Hani Tavakoli; Epstein, David; Samolov, Branka; Olsson, Monica; Naess, Karin; Oscarson, Mikael; Teaer Fahnehjelm, Kristina
ABSTRACT: Background: Fabry disease (FD) is an X-linked lysosomal disease, in which diagnosis is often established several years after onset of symptoms. Ocular manifestations can occur in childhood and be a clue to earlier diagnosis. The aim was to report ocular outcome and visual quality of life (QoL) in patients with FD. Material and methods: FD-patients recruited from Karolinska University Hospital underwent ophthalmological examinations including best corrected visual acuity (BCVA), refraction, biomicroscopy, optical coherence tomography, keratometry, review of medical records and QoL Inventories. A total severity score (TSS), as estimated via Fabry Stabilization Index, was calculated. Results: Twenty-six FD-patients (16 men) mean age 36.4 years (range 5.0–63.5 years) were included. BCVA was median 1.0 (range 0.5–1.6). Conjunctival blood vessel tortuosity occurred in 15/26 patients, chemosis in 2/26 patients, cornea verticillata in 23/26 patients, lens opacities in 19/26 patients, and tortuous or dilated retinal vessels in 20/25 patients. Group-wise comparisons of adult patients showed no differences regarding age, TSS, or ocular parameters. Overall, TSS was correlated to age (r = 0.53, p = 0.02). A linear regression model showed that age and sex explained 38% of the variance in TSS. Keratometry did not reveal corneal ectasia in any of the 12 patients examined. VFQ 25 in 15 patients showed a high median composite score, 93.6 (range: 78.1–100). Conclusions: BCVA in FD-patients was good despite corneal and lens pathology. Ocular variables did not show an association with TSS in adult patients. Corneal or lens opacities should also lead to a suspicion of FD in children.